Anticipatory response model for multi-agent based energy management system in a standalone microgrid - Khan M.R.B.; Pasupuleti J.; Jidin R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Distributed power generation; Energy management systems; Energy resources; Forecasting; Game theory; Multi agent systems; Renewable energy resources; Anticipatory response; Auto regressive models; Centralized controllers; Micro grid; Multi agent; Multiagent architecture; Predictive algorithms; Renewable energies; Electric load dispatching